KONSEP ISLAM TENTANG PENDIDIKAN - M. NUR (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2024)
The purpose of this research is to find out the Islamic concept of education. The method used is qualitative with literature study. The results of this study indicate that the concept of education in Islam which refers to the teachings of the Qur'an and hadith, is very clearly outlined in the story in the story of Luqman. M. Sayyid Ahmad Al-Musayyar quoted several verses of the Qur'an in Surah Luqman. (1) Cultivation of Faith (2) Pillars of Education (3) Social EthicsThe purpose of education must be based on education itself. At the very least, this is based on the basic concepts of man, nature, and science and with consideration of the basic principles John White states that those who know the purpose of education best are those who know the most about education, namely teachers. Islamic education methods include (1) The method of education in groups or called reciprocal education. (2) The method of instructional education (3) The method of educating by telling stories. (4) Methods of education through guidance and counseling (5) gentleness and tenderness with the aim of guiding towards the truth (6) Methods of giving examples and examples (7) Methods of educating by discussion (8) Question and answer methods (9) Methods of educating by using parables. (10) Targhib and Tarhib method.